(untitled) (Fiep Bulletin - online, 2012)
The primal propose of this investigation consists in the analysis of motivations for the candidature of Portugal to major sports events; the balance made up of these same events; the benefits accruing to the country and for the sport and the differences between the candidates of the 2005 World Cup and The Ryder Cup 2018. Having opted for a qualitative research for analysis of our corpus, obtained the relevant categories for analysis. Since the semantic unit of analysis was defined a priori, we start the formal definition of 6 units of analysis that emerged from interviews, sub-divided into 31 context units. The sample consisted of three individuals, as follows: the Director of the Victoria Golf Course and Secretary General of the Golf Club of Vilamoura, the Marketing Director of Ocean Golf and the Secretary General of the Portuguese Golf Federation. Data collection was crafted from semi-structured interviews. The interviews led us to conclude that the Golf sport’s event held in Portugal brings practitioners, caregivers and supporters to promote and encourage domestic tourism, achieving a maximization of state and private investment made in promotion of tourism in hotels, leisure activities on offer. The Portuguese do not adhere to the Golf Club and related events, for cultural reasons or a connotation of Golf a sport elitist and expensive. A country like Portugal coexists with some remaining gaps to appear as a "strong candidate" near absence of internationally renowned sportsmen. Another constraint to the achievement of major events is the need for government support, which happened in Portugal but in a timely and unprecedented.